A Letter for Missing and Disappeared Archives - Iralu, Elspeth (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
In this letter, Elspeth Iralu initiates a time-travelling correspondence with her paternal grandfather, Vichazelhu Iralu, about his dreams for the Naga sovereignty movement. The letter grieves the loss of personal and political archives that were stolen, disappeared, and destroyed through processes of colonization. Iralu offers letter-writing, shaped by Naga modes of storytelling, as an anticolonial epistemology that enacts Naga sovereignty in the here and now.